KINERJA DINAS TENAGA KERJA DAN TRANSMIGRASI DALAM MELAKSANAKAN PROGRAM PENGURANGAN ANGKA PENGANGGURAN - Hanifah, Indri; Pratidina, Ginung; Seran, M.YGG (Jurnal Governansi, 2018)
The purpose of this research is to know the performance of Dinas Tenaga. Work and Transmigration in implementing the unemployment reduction program of Bogor City. The theory used to measure the performance of Disnakertrans in implementing unemployment reduction program of Bogor City is the theory put forward by Dwiyanto (in Pasolong 2007) on bureaucratic performance measures. This theory says that there are 6 (six) indicators such as productivity, quality, responsiveness, service, accountability, and responsibilitas. The method in this research using descriptive qualitative research method. While the data analysis technique used is using Interactive model developed by Miles and Huberman (in Sugiyono 2010), which includes data reduction, display data, and conclusion drawing / verivication data collection techniques used are interviews, direct observation and documentation. The informants that the researchers took were two types of informants, firstly some employees of Disnakertrans were considered to be involved in the program of reduction of unemployment rate and second was 2 participants who had attended the program. The results of research on the performance of the Department of Manpower and Transmigration in implementing the program of reduction of unemployment rate in the city of Bogor is good. Because so far, the Manpower has done everything possible in implementing the existing program despite some obstacles. With this result, it is expected that the Manpower and Transmigration Office will be able to overcome the obstacles experienced and the better performance and reduce the unemployment rate in Bogor city today. Keywords: Performance, Bureaucratic Performance, Unemployment Program